Peningkatan Prestasi Belajar PAI Materi Wudhu Melalui Metode Demonstrasi Pada Siswa Kelas II SD Alam QU Ainur Rahmah - Rahmawati, Kumala Sari; Sucy, Rahma Dhia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine whether the demonstration method can improve student achievement in ablution material for second-grade students at SD Alam Qu Ainur Rahmah. This classroom action research uses the demonstration method by demonstrating or showing students a process or situation being studied, thereby enhancing their understanding of the lesson. This research is a CAR with three cycles through four stages: planning, implementation, observation, and reflection. The subjects of this study were 32 students. The hypothesis proposed is that if the demonstration method is used effectively, it can improve student achievement in Islamic Religious Education (PAI) for second-grade students at SD Alam Qu Ainur Rahmah. The success indicator is 75% with a Minimum Competency (KKM) of 75. Data collection techniques include observation. Data analysis techniques use formulas to determine average values and percentages. The results of the study showed that learning achievement in cycle I was 44% or 14 students with a KKM of 75, cycle II was 56% or 18 students with a KKM of 75 and in cycle III was 81% or 26 students for the material of the pillars of ablution and 87.5% or 28 students for the material of the sunnah of ablution with a KKM of 75. The increase in student learning achievement from cycle I to cycle II was 12% with a KKM of 75, the increase in achievement from cycle II to cycle III with the material of the pillars of ablution was 25% and in the material of the sunnah of ablution was 31.5%.